Dipole relaxation, dielectric and electric properties of PbWO₄ crystals - Shevchuk, V.N.; Kayun, I.V. (Functional Materials, 2005)
Experimental dependences of permittivity for undoped PbWO₄ single crystals at 1 kHz frequency in 290-550 К temperature range are considered. The ε(Т) curve runs under heating and cooling are different. The ε(Т) function under heating is characterized by groups of narrow maxima at 290-330 К and 330-400 К, the former being predominating. At 400-470 К, the ε(Т) dependence is linear, while above 470 К, the function is nearly exponential. After the high-temperature heat treatment of a sample, a multistage relaxation process of ε values within limits of 25 to 30 is observed at 290 К. The features of ε(Т) at low temperatures are defined by the dipole polarization and hopping mechanism of the charge exchange between complex dipole associates. The pairs of lead and oxygen vacancies (dipolons) are predominating intrinsic defects of the crystal structure; those defects form more complex dipole associates. Экспериментальные зависимости диэлектрической проницаемости нелегированных кристаллов PbWO₄ на частоте 1 кГц рассматриваются при температурах Т = 290-550 К. Ход кривой ε(Т) при нагревании и при охлаждении различен. Функция ε(Т) при нагревании характеризуется наличием групп узких максимумов при 290-330 К и 330- 400 К с доминированием первых. При 400-470 К наблюдается линейная зависимость ε(Т), выше 470 К закон изменения ε близок к экспоненциальному. После высокотемпературного нагревания образца наблюдается при 290 К многостадийный процесс восстановительной релаксации значений ε в пределах 25-30. Дипольная поляризация и прыжковый механизм обмена зарядами между сложными дипольными ассоциатами определяют особенности ε(Т) при низких температурах. Доминирующими дефектами структуры являются пары вакансий свинца и кислорода - диполоны, на основании которых образуются более сложные дипольные комплексы. Експериментальнi залежностi дiелектричної проникностi нелегованих кристалiв PbWO₄ на частотi 1 кГц розглядаються при температурах Т = 290-550 К. Хiд кривої ε(Т) при нагрiваннi та при охолодженнi вiдмiнний. Функцiя ε(Т) при нагрiваннi характеризується наявнiстю груп вузьких максимумiв при 290-330 К та 330-400 К з домiнуванням перших. При 400-470 К спостерiгається лiнiйна залежнiсть ε(Т), вище 470 К закон змiни ε близький до експоненцiйного. Процес вiдновної релаксацiї значень ε у межах 25-30 при 290 К пiсля високотемпературного нагрiвання здiйснюється в декiлька стадiй. Дипольна поляризацiя та стрибковий механiзм обмiну зарядами мiж складними дипольними асоцiатами визначають особливостi ε(Т) при низьких температурах. Домiнуючими дефектами структури є пари вакансiй свинцю та кисню - диполони, на основi яких утворюються складнiшi дипольнi комплекси.